Using ADDIE Model to Appraise MOOC English for Non-Academic Staffs (ENAS) Designed for University Non-Academic Staffs Amid the COVID 19 Outbreak - Kartika Nuswantara; Banu Prasetyo; Gita Widi Bhawika; Ni Wayan Suarmini (JURNAL SOSIAL HUMANIORA (JSH), 2021)
To help universities non-academic staffs maintain their productivity amid the COVID 19 outbreak, MOOC ENAS was developed. To guarantee the eligibility of the program, through this research, ADDIE model was employed to evaluate the course plan. Step 1 and 2 out of the whole 5 steps of ADDIE were used to describe qualitatively about the course design. Using an online questionnaire, the authors received 110 responses and were able to demonstrate that the design had the quality for a good course design. This was led by the results of investigation on the participants’ background correspond to the course plan including the description and objectives. It was figured out that the design was able to accommodate the participants’ language learning demands. The course design facilitated students learning by serving their education background, their workplace origin, and their already existing language learning experience. However, the study was lacking in the generalizability. To serve this, further research is needed by adding quantitative data so that the results of the evaluation could be presented in numbers that were more accurate and elusive. Finally, in terms of design, the MOOC ENAS is quite accommodating to be further continued into development of course content, implementation, and evaluation as assigned in ADDIE Model.